Evaluasi Kinerja Guru untuk Meningkatkan Mutu Pembelajaran di SDN Lidah Wetan IV Surabaya - Salsabila, Putti Erian; Aini, Nushah; Lintang, Rehan Puspa; Trihantoyo, Syunu; Nuphanudin, Nuphanudin (TSAQOFAH, 2024)
Teacher performance evaluation is a process of assessment and supervision carried out systematically to obtain real results and will be used as a reference for further performance development. Teacher performance evaluation is very important to determine the quality of a teacher in doing his job. By knowing the weaknesses or shortcomings of a teacher, the principal can plan a training program that is in accordance with the quality of the teacher. Good teacher quality is very important in the quality of learning, both to achieve learning goals at school and student activeness in the learning process. This article aims to analyze how to evaluate teacher performance at SDN Lidah Wetan IV Surabaya. The method used in this research is qualitative method. Data collection techniques in the research are observation and interview. The subjects in this study were principals, teachers, and students. The results showed that the Principal of SDN Lidah Wetan IV Surabaya is quite good in evaluating teacher performance, this is evidenced by the principal in providing guidance, supervision, and motivation to teachers so that teacher performance can experience good development.